Linguistic Assumptions and Lexicographical Traditions in the African Languages - van Wyk, E.B. (Lexikos, 1995)
Two lexical traditions exist in the African languages of South Africa. According to the word tradition, lemmas are based on complete written words, and there is a one-to-one correspondence between written words and lemmas. According to the stem tradition, lemmas are based on the stems of written words without their prefixes. It is pointed out that the difference between these traditions lies mainly in the treatment of nouns. It is also shown that the stem tradition, uncritically regarded by many linguists as more scientific, is based on incorrect assumptions with reference to the morphology of nouns, that it is not applied consistently and that it is less user friendly. It is concluded that the word tradition is based on sounder lexicographical principles.